An in vitro alveolar epithelial cell model recapitulates LRRK2 inhibitor-induced increases in lamellar body size observed in preclinical models. (February 2021) - Harney, Julie; Bajaj, Piyush; Finley, James E.; Kopec, Anna K.; Koza-Taylor, Petra H.; Boucher, Germaine G.; Lanz, Thomas A.; Doshna, Colleen M.; Somps, Christopher J.; Adkins, Karissa; Houle, Christopher
Abstract: Alveolar type II (ATII) epithelial cells contain lamellar bodies (LBs) which synthesize and store lung surfactants. In animals, the inhibition or knockout of leucine-rich repeat kinase 2 (LRRK2) causes abnormal enlargement of LBs in ATII cells. This effect of LRRK2 inhibition in lung is largely accepted as being mediated directly through blocking of the kinase function; however, downstream consequences in the lung remain unknown. In this work we established an in vitro alveolar epithelial cell (AEC) model that recapitulates the in vivo phenotype of ATII cells and developed an assay to quantify changes in LB size in response to LRRK2 inhibitors. Culture of primary human AECs at the air-liquid interface on matrigel and collagen-coated transwell inserts in the presence of growth factors promoted the LB formation and apical microvilli and induced expression of LRRK2 and ATII cell markers. Treatment with a selective LRRK2 inhibitor resulted in pharmacological reduction of phospho-LRRK2 and a significant increase in LB size; effects previously reported in lungs of non-human primates treated with LRRK2 inhibitor. In summary, our human in vitro AEC model recapitulates the abnormal lung findings observed in LRRK2-perturbed animals and holds the potential for expanding current understanding of LRRK2 function in the lung. Highlights: Alveolar epithelial cells express lamellar bodies and ATII markers in transwell model over 14 days. Imaging assay detects increases in LB size following treatment with LRRK2 inhibitor. LRRK2 inhibition in alveolar transwell model recapitulates lung effects in vivo.